Moldes e moldagens: instrumentos de proteção, preservação e perpetuação da obra de Antonio Francisco Lisboa - Alexandre Ferreira Mascarenhas (2013)
This doctorate degree research paper aims to give value to the techniques of execution of moulds and casts direct on original sculptures by Antonio Francisco Lisboa, Aleijadinho the greatest exponent of baroque sculpture in Minas Gerais. It is important to point out not only the importance of using these techniques in restoration or conservation of immovables (facades and historical plafonds|ceilings) and/or movables (sculptures), but, mainly their use as conservation, preservation, diffusion and perpetuation tool of the work per se and consequently, of the artist whose importance is an integrating part of a given society and in some cases, considered as cultural and identity heritage. In addition to this, we noticed that the replicas casts have higher quality and quantity ornamental, stylistic and iconographic information than the original works, in most cases, exposed the actions from the weather and human vandalism, and are quite degraded. Therefore, the recovery of these techniques is deemed necessary since the labour performing in this work segment is scarce and, particularly, technical and practical information to be approached in this research has a vast field of applications in the practice, for it shall contribute to various levels of conservation, restoration, valuing, diffusion and perpetuation of these techniques and mainly the work by Aleijadinho.